Pengembangan LKPD Matematika Berbasis PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas 6 SDN 106155 Tandam Hilir - Eny Ramadhani; Ahmad Calam; Syahrina Anisa Pulungan (cendekia citra gemilang, 2026)
This study aimed to develop a Problem-Based Learning (PBL)-based mathematics student worksheet (Lembar Kerja Peserta Didik/LKPD) that is valid, practical, and effective in improving the problem-solving skills of sixth-grade students at SDN 106155 Tandam Hilir on fraction topics. The study employed a Research and Development (R&D) approach using the 4D development model, consisting of the define, design, develop, and disseminate stages. The research subjects included sixth-grade students, material experts, media experts, and classroom teachers. Data were collected through observation, interviews, questionnaires, and problem-solving ability tests. The data were analyzed using descriptive quantitative and qualitative techniques through validity, practicality, and effectiveness assessments. The findings indicated that the developed PBL-based mathematics worksheet met the feasibility criteria based on evaluations from material and media experts. The worksheet also received positive responses from teachers and students, indicating its practicality in classroom implementation. Furthermore, the use of the PBL-based worksheet improved students’ mathematical problem-solving abilities, as reflected in the increase in learning outcomes after the instructional process. Therefore, the developed PBL-based mathematics worksheet can be utilized as an innovative instructional material to support active, contextual, and student-centered mathematics learning in elementary schools.